Levulinic acid: a novel sustainable solvent for lignin dissolution - Melro, Elodie (2020)
Lignin is a natural, renewable resource with potential to be used in biomaterials. Due to its complex structure, its efficient dissolution is still challenging, which hinders its applicability at large scale. This challenge become harder considering the current need of sustainable and environmentally friendly solvents. To the best of our knowledge, this work reports for the first time the dissolution of kraft lignin in levulinic acid, a "green" solvent, and compares its efficiency with common carboxylic acids and sulfuric acid. It has been found that levulinic acid has a high capacity to dissolve kraft lignin at room temperature (40 wt% solubility), and it efficiency is not compromised when diluting the acid with water (up to 40 wt% water content). the Kamlet-Taft pi* parameter of the different acidic solvents was estimated and found to correlate well with their solubility performance. Lignins previously dissolved in levulinic and formic acids were selected to be regenerated and minor differences were found in thermal stability and morphological structure, when compared to native kraft lignin. However, an increase in the content of the carbonyl groups in the regenerated lignin material was observed. (C) 2020 Elsevier B.V. All rights reserved.